ARM Assembly Language with Hardware Experiments - Elahi, Ata; Arjeski, Trevor (Springer, 2015)
This book provides a hands-on approach to learning ARM assembly language with the use of a TI microcontroller. The book starts with an introduction to computer architecture and then discusses number systems and digital logic. The text covers ARM Assembly Language, ARM Cortex Architecture and its components, and Hardware Experiments using TILM3S1968. Written for those interested in learning embedded programming using an ARM Microcontroller. © Springer International Publishing Switzerland 2015.
Keywords: ARM microcontrollers; ARM processors; Arm cortices; Assembly language; Assembly languages (Electronic computers); Microprocessors; Computer architecture; Computer hardware; Digital logic; Education; Embedded programming; Hardware; Hardware experiment; Microcontrollers; Number system; Numbering systems; Programming; dept.csc; faculty_collection